GhGLK1 a Key Candidate Gene From GARP Family Enhances Cold and Drought Stress Tolerance in Cotton - Liu, Jiangna; Mehari, Teame Gereziher; Xu, Yanchao; Umer, Muhammad Jawad; Hou, Yuqing; Wang, Yuhong; Peng, Renhai; Wang, Kunbo; Cai, Xiaoyan; Zhou, Zhongli; Liu, Fang (Frontiers in Plant Science, 2021)
Drought and low temperature stresses are the most prominent abiotic stresses affecting cotton. Wild cotton being exposed to harsh environments have more potential to cope with both biotic and abiotic stresses. Exploiting wild cotton material to induce resistant germplasm would be of greater interest. The candidate gene was identified in the BC2F2 population among G. tomentosum and G. hirsutum as wild male donor parent noted for its drought tolerance and the recurrent parent, and a high yielding but drought susceptible species by GBS mapping. Golden2-like (GLK) gene, which belongs to the GARP family, is a kind of plant-specific transcription factor that was silenced by virus-induced gene silencing (VIGS). Silencing of GhGLK1 in cotton results in more damage to plants under drought and cold stress as compared to wildtype. The overexpression of GhGLK1 in Arabidopsis thaliana showed that the overexpressing plants showed more adaptability than the wild type after drought and cold treatments. The results of trypan blue and DAB staining showed that after drought and cold treatment, the leaf damage in GhGLK1 overexpressed plants was less as compared to the wild type, and the ion permeability was also lower. This study suggested that the GhGLK1 gene may be involved in the regulation of drought and cold stress response in cotton. Our current research findings add significantly to the existing knowledge of cold and drought stress tolerance in cotton.